'Rational' Farmers and the Emergence of Modern Accounting in Danish Dairying - Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2017)
We argue that Danish agriculture provides an ideal opportunity to understand how and why modern accounting emerged. Denmark underwent an unusually rapid and successful agricultural transformation in the second half of the nineteenth century, largely based on dairying, for which we present unique 'real time' data on the process of the development of accounting. We observe that economic actors first argued for the introduction of modern accounting at a time of crisis during the Napoleonic Wars and immediately after, when the proscriptive arguments offered failed to take hold. Then, in the 1850s and 1860s, a group of 'rational farmers'- owners and administrators of landed estates - made a second attempt. During this latter period, they succeeded in spreading their ideas: initially to their peers, but later even to the peasantry through the cooperative movement, thus transforming agricultural practice in their wake. We analyze this within a theoretical framework borrowed from the international relations literature, and see the rational farmers as an example of the creation of an 'epistemic community': they emerged during a period of uncertainty, offered interpretations based on their normative understanding of reality, and finally institutionalized praxis through for example scientific journals and schooling.
Keywords: M41; N53; 330; Accounting; bookkeeping; dairies; Denmark